Electrochemical investigation on the corrosion inhibition of mild steel by Quinazoline Schiff base compounds in hydrochloric acid solution - Khan, G.; Basirun, Wan Jefrey; Kazi, S.N.; Ahmed, P.; Magaji, L.; Ahmed, S.M.; Khan, G.M.; Rehman, M.A. (Elsevier, 2017)
The inhibitory effect of two Schiff bases 3-(5-methoxy-2-hydroxybenzylideneamino)-2-(-5-methoxy-2-hydroxyphenyl)-2,3-dihydroquinazoline-4(1H)-one (MMDQ), and 3-(5-nitro-2-hydroxybenzylideneamino)-2(5-nitro-2-hydroxyphenyl)-2,3-dihydroquinazoline-4(1H)-one (NNDQ) on the corrosion of mild steel in 1 M hydrochloric acid were studied using mass loss, potentiodynamic polarization technique and electrochemical impedance spectroscopy measurements at ambient temperature. The investigation results indicate that the Schiff Bases compounds with an average efficiency of 92% at 1.0 mM of additive concentration have fairly effective inhibiting properties for mild steel in hydrochloric acid, and acts as mixed type inhibitor character. The inhibition efficiencies measured by all measurements show that the inhibition efficiencies increase with increase in inhibitor concentration. This reveals that the inhibitive mechanism of inhibitors were primarily due to adsorption on mild steel surface, and follow Langmuir adsorption isotherm. The temperature effect on the inhibition process in 1 M HCl with the addition of investigated Schiff bases was studied at a temperature range of 30–60 °C, and the activation parameters (Ea, ΔH and ΔS) were calculated to elaborate the corrosion mechanism. The differences in efficiency for two investigated inhibitors are associated with their chemical structures.